THE RELATIONSHIP BETWEEN NURSES' PERCEPTIONS AND SELF-EFFICACY IN IMPLEMENTING PALLIATIVE CARE IN THE INTENSIVE CARE UNIT - Theresia Avila Kurnia; Yanny Trisyani; Ayu Prawesti (Belitung Raya Foundation, Indonesia, 2019)
Background: The increasing need for palliative care in intensive care unit (ICU) is indicated by the increasing number of patients with critical and terminal conditions or life-threatening diseases. A comprehensive handling through palliative care by nurses is needed. Self-efficacy is the main predictor that influences the application of palliative care in ICU. Therefore, nurses should have high self-efficacy in order to provide qualified palliative care for patients and their families. Objective: This study aimed to analyze the relationship between perceptions and self-efficacy of nurses in applying palliative care in ICU. Methods: This study was a correlational study with a cross sectional approach. The sampling technique used was total sampling, which involved all nurses who were actively working at the Bandung General Hospital during the study. There were 127 people in total. Data were collected using questionnaires. Descriptive analysis was used for the univariate analysis and Pearson correlation test was used for bivariate analysis. Results: The results of univariate analysis showed that the majority of respondents had high self-efficacy (56.7%) and negative perceptions (52%) related to palliative care in the intensive room. Based on the results of bivariate analysis, there was a significant relationship between perception and self-efficacy variables (p value = 0.000). Conclusion: The results showed that high number of respondents had negative perceptions related to their competences in implementing palliative care in the ICU. Therefore, socializations and trainings related to this are needed, which focus on nurses' beliefs in their abilities.